Resilience and Innovation: The European Governance System's Response to COVID-19 - Silvia PASCHINA; Mohamed HAMZA BENAMMI (Revista de Management Comparat International)
The COVID-19 pandemic presented an unprecedented challenge to European governance systems, testing their capacity to respond effectively to a multifaceted crisis. We conducted a systematic search between January and February 2023 of originally published articles from three electronic databases, such as Scopus, Google Scholar, and OECD iLibrary, including papers that were published in the last decade. This review provides a concise overview of the key aspects of European governance in the face of the pandemic. It discusses the initial hurdles in coordination and solidarity among member states, the strain on healthcare systems, economic repercussions, and the imperative for digital transformation. The review presents the current scope of research, highlights the limitation, and provides recommendations for future perspectives.